Understanding the Impact of Bad Debt on XYZ Savings and Loan Cooperative - Syahnanda, Muhammad Daffa Aqila; Susilowati, Endah (Equity: Jurnal Akuntansi, 2025)
This study aims to explore the understanding of the influence of credit provision by Savings and Loan Cooperatives (KSP) on employee welfare and productivity in PT HM Sampoerna Tbk. Using a qualitative approach, this study focuses on deepening the perceptions, experiences, and impacts felt by KSP members in utilizing credit facilities. The study will highlight how easy access to credit affects personal financial management, job satisfaction, motivation, and possible changes in employee performance and loyalty. Initial findings indicate that although credit from KSP can be a short-term financial solution, its impact is complex. On the one hand, credit can improve family economic stability; on the other hand, it can also cause psychological stress due to debt burden. This study will also explore how KSP credit directly or indirectly affects work productivity, for example through reduced absenteeism, increased focus, or conversely, disruption due to financial stress.